Subdural enhancement of the spinal cord during the contrast-enhanced magnetic resonance imaging after resection of posterior cranial fossa tumor in children - G. V. Tereschenko; S. S. Ozerov; E. V. Kumirova; A. V. Artemov (Вестник рентгенологии и радиологии, 2016)
Diagnosis of spinal leptomeningeal metastases in children with brain tumors is currently performed using magnetic resonance imaging (MRI) with contrast enhancement. In some cases, non-specific contrast agent accumulation along the meninges is detected on MRI in the postoperative period, which can be misdiagnosed as metastases, or can obscure true metastasis to the spinal cord. The article presents a clinical example of this phenomenon.